2001
DOI: 10.1002/etc.5620200622
|View full text |Cite
|
Sign up to set email alerts
|

Identification of androstenedione in a river containing paper mill effluent

Abstract: Effluent from a paper mill discharging into the Fenholloway River, Taylor County, Florida, USA, contains chemicals that masculinize females of the resident population of eastern mosquitofish (Gambusia holbrooki), as evidenced in females by elongated anal fins, which is normally a male-specific trait. To identify androgenic components in the effluent, water collected from the Fenholloway River and a control tributary was fractionated using solid-phase extraction and reverse-phase high-performance-liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(73 citation statements)
references
References 46 publications
5
66
1
1
Order By: Relevance
“…It should be noted that in the effluent studied here, cholesterol is frequently found in similar quantities to phytosterols and thus is also a potential precursor to steroidal compounds as weil. Recently, androstenedione was identified by liquid chromatography/ mass spectrometry as one of two androgen-like compounds within a kraft mill receiving water [24]. River receiving water fractions induced androgen receptor-dependent transcriptional activity in transient transfection cell cultllre assays.…”
Section: In Vitra Goldfish Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that in the effluent studied here, cholesterol is frequently found in similar quantities to phytosterols and thus is also a potential precursor to steroidal compounds as weil. Recently, androstenedione was identified by liquid chromatography/ mass spectrometry as one of two androgen-like compounds within a kraft mill receiving water [24]. River receiving water fractions induced androgen receptor-dependent transcriptional activity in transient transfection cell cultllre assays.…”
Section: In Vitra Goldfish Experimentsmentioning
confidence: 99%
“…[22] have shown that byproduets of microbial-degraded stigmastanol and ß-sitosterol ean exert morphogenie effeets in female mosquitotish that are similar to those observed by Turner [23] and Howell et al [13] on exposure to androgens. Recently, androstenedione was identified as one of two androgenie compounds within BKMEreeeiving water fraetions eoIIeeted where a population of maseulinized mosquitofish was found [24].…”
mentioning
confidence: 99%
“…In 1997 paper mill effluent was revealed to cause androgenic effects on mosquitofish and livebearer fish [15]. In 2001 masculinized fish were found in the Fenholloway River east of Perry, Florida, USA containing androstenedione [16]. Another study [17] confirmed that female mosquitofish were masculinized by short-term exposures to high concentration of androstenedione.…”
Section: Introductionmentioning
confidence: 97%
“…It is reported that EDCs could interfere with reproduction and development, induce hermaphroditism of aquatic organisms [1], and increase the possibility of breast and testicular cancers in humans [2]. Natural and synthetic steroids have been regarded as the most important members of EDCs which could cause adverse effects on aquatic organism at the low ng/L level [3,4]. In addition to excretion of natural steroids by human and animals, synthetic steroids have also been widely used in our daily life and livestock industry for various purposes, such as contraception, human and veterinary therapy, and growth promoters.…”
Section: Introductionmentioning
confidence: 99%